Genetic and phenotypic correlations among reproductive and productive traits of Nelore bulls - Dias, Juliano Cesar; Andrade, Venício José de; Martins, Jorge André Matias; Emerick, Lucas Luz; Filho, Vicente Ribeiro do Vale (Pesquisa Agropecuaria Brasileira, 2008)
The aim of this work was to estimate genetic and phenotypic correlations for sexual reproductive and productive traits using a Multiple Trait Derivative-Free Restricted Maximum Likelihood (MTDFREML) methodology in 579 Nelore bulls, raised under pasture. The reproductive traits analyzed were scrotal circumference, testicular consistency, testicular volume, testicular shape, length and width of right and left testicles, physical (motility and vigor) and morphological (major and minor, and total sperm defects) semen traits, and breeding soundness evaluation. Genetic correlations between scrotal circumference and body weight, testicular volume, motility, vigor, minor sperm defects, total sperm defects and breeding soundness evaluation were, respectively, 0.72, 0.99, 0.72, 0.60, -0.67, -0.12 e 0.64, showing favorable associations of scrotal circumference and the characteristics related. Phenotypic correlations of major magnitude found among ages and the above-related characteristics suggested to be the body weight the major factor affecting the reproductive performance of those animals. Genetic correlations among breeding soundness evaluation, body weight, scrotal circumference, testicular volume, major sperm defects and total sperm defects were, respectively, 0.19, 0.64, 0.71, -0.47 e -0.58.